Comparative study of some macro & micro elements in milk samples from Abuja, Nigeria using microwave plasma atomic emission spectroscopy (MP-AES) and flame atomic absorption spectroscopy (F-AAS) methods - S.J, Salawu; M.D, Faruruwa; Y, Mohammed; S, Abubakar (International Journal of Advanced Chemistry, 2022)
A comparative study was carried out for the determination of calcium, magnesium, iron and zinc contents in two brands of powdered milk samples, using the Microwave Plasma Atomic Emission Spectroscopy (MP-AES) and Flame Atomic Absorption spectroscopy (F-AAS) methods. The powdered milk samples were collected and placed in a muffle furnace at 550Â°C for 6 hours, and the ash contents obtained was used for the sample preparation. The percentage recoveries for the spikes were as follows: for MP-AES determination; the recoveries for the milk samples were within the range (116.9 â€“ 163.1%) for calcium; (51.8 â€“ 78.8%) for magnesium; (110.9 â€“ 125.4%) for iron; (90.7 â€“ 92.9%) for zinc. For FAAS determination; the recoveries for the milk samples were within the range (51.1 â€“ 83.6%) for calcium; (52.2 â€“ 61.9%) for magnesium; (77.7 â€“ 84.8%) for iron; (46.5 â€“ 71.7%) for zinc. The percentage recoveries showed a better recovery with MP-AES than the F-AAS method. The analysis of variance conducted using One way ANOVA method shows that there is no significant difference between the two methods used for the analysis, as the P-values (calculated probability) obtained were higher than 0.05. The values obtained for Ca, Mg, Fe and Zn content shows that only Ca was found to be within WHO/FAO standard, while Mg, Fe and Zn were found to be below the WHO/FAO standard. It is highly recommended that a 100g of any of the powdered milk used for the research work be consumed per day in order to meet up with the RDA per day, or other sources of these elements to be considered.Â